Political violence in the G5 Sahel Countries (2018-2023): An application of ACLED’s conflict index methodology - Marivoet, Wim; Hema, Aboubacar; Nsaibia, Heni (International Food Policy Research Institute, 2024)
Over the past decade, the G5 Sahel countries (Mauritania, Mali, Burkina Faso, Niger, and Chad) have seen their security situation substantially worsen, following a combination of political instability, jihadist insurgencies and the proliferation of local militias. To better capture the multifaceted nature of conflict and political violence in the G5 Sahel region, this study applies the conflict index methodology developed by the Armed Conflict Location & Event Data Project (ACLED) to the second-level administrative entities within each country between 2018 and 2023. The outcome of this temporally and spatially refined conflict profile is projected in several tables, graphs and maps, which indicate: (i) that political violence has intensified over the period considered; (ii) that most of the conflict events were concentrated in the tri state border area of Liptako-Gourma; and (iii) that political violence is far from uniform across its underlying dimensions, suggesting that different strategies might be needed to restore security. In methodological terms and using the results from the temporal analysis, this study also introduces a distinction between protracted and transient forms of political violence, which provides additional insight to the index dimensions of deadliness, danger, diffusion, and fragmentation.